2017
DOI: 10.1902/jop.2017.170004
|View full text |Cite
|
Sign up to set email alerts
|

Photometric CIELAB Analysis of the Gingiva: A Novel Approach to Assess Response to Periodontal Therapy

Abstract: Results of this study suggest potential benefit in using photometric analysis to assess gingival changes after therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 19 publications
2
20
1
2
Order By: Relevance
“…In an attempt to circumvent the subjectivity of examiner scoring, non‐invasive methods based on digital technologies were introduced more recently. These methods mainly aim at measuring the volumetric or color changes that occur in the gingival tissues due to plaque‐induced inflammation . Although their application would be highly desirable in the diagnosis of gingivitis, no histologic validation of these instruments is currently available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to circumvent the subjectivity of examiner scoring, non‐invasive methods based on digital technologies were introduced more recently. These methods mainly aim at measuring the volumetric or color changes that occur in the gingival tissues due to plaque‐induced inflammation . Although their application would be highly desirable in the diagnosis of gingivitis, no histologic validation of these instruments is currently available.…”
Section: Methodsmentioning
confidence: 99%
“…Although their application would be highly desirable in the diagnosis of gingivitis, no histologic validation of these instruments is currently available. Moreover, few studies have evaluated their reliability in subjects with gingivitis . While some studies reported a positive association between the gingival volume and GI changes (without reporting the statistical strength of the association), other studies failed to find a significant correlation between colorimetric assessments and variations in GI .…”
Section: Methodsmentioning
confidence: 99%
“…These methods mainly aim at measuring the volumetric or color changes that occur in the gingival tissues due to plaque-induced inflammation. [49][50][51][52][53][54][55][56] Although their application would be highly desirable in the diagnosis of gingivitis, no histologic validation of these instruments is currently available. Moreover, few studies have evaluated their reliability in subjects with gingivitis.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…Moreover, few studies have evaluated their reliability in subjects with gingivitis. 49,54,56 While some studies reported a positive association between the gingival volume and GI changes (without reporting the statistical strength of the association), 49 other studies failed to find a significant correlation between colorimetric assessments and variations in GI. 56 Moreover, additional aspects, including need for standardized conditions for their use, restriction of colorimetric assessments to the buccal attached gingiva of anterior teeth and need for specific adjustments for colorimetric evaluations of pigmented gingival tissues in specific ethnic groups, limit the potential to apply these technologies reliably or pragmatically to define a GC.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…This method has been used in various investigations to assess differences in color perception between teeth, 19 shade guides, 20,21 and observers. 22,23 Moreover, image analysis is applied in shade matching, [24][25][26] communication between dentists and laboratory technicians, 27,28 diagnosis of gingival inflammation, [29][30][31] oral lesions detection, 32 and evaluation of bleaching results. [33][34][35][36][37] A very high and statistically significant correlation was found between the spectrophotometer and digital imaging analysis for all CIE L*a*b* color values.…”
mentioning
confidence: 99%